2012
DOI: 10.3390/molecules171112657
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Interactions between Major Phenolic Compounds Found in ‘Ataulfo’ Mango Pulp: Chlorogenic, Gallic, Protocatechuic and Vanillic Acids

Abstract: Phenolic compounds are known to have antioxidant capacity; however, there is little information about molecular interactions between particular phenolics found in fruits at different developmental stages. Therefore, the total antioxidant capacity of the phenolic compounds of a fruit may not correspond to the sum of individual antioxidant capacity given by antioxidants from that tissue. In this study, individual antioxidant capacity and the interactions of four major phenolic compounds (chlorogenic, gallic, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 23 publications
10
84
0
2
Order By: Relevance
“…Furthermore, A. judaica was revealed to have sesquiterpene lactones [36] flavonoids [35,40] and high phenolic contents [39,41,43]. These compounds were reported to have multiple biological effects including antiinflammatory, antioxidant [43] chemopreventive and anticancer activities [44]. The results reported herein also revealed that both doses A. judaica extract had no toxic effect and this result is in line with a study conducted with Nofal et al [45] who confirmed the safety of A. judaica extracts.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, A. judaica was revealed to have sesquiterpene lactones [36] flavonoids [35,40] and high phenolic contents [39,41,43]. These compounds were reported to have multiple biological effects including antiinflammatory, antioxidant [43] chemopreventive and anticancer activities [44]. The results reported herein also revealed that both doses A. judaica extract had no toxic effect and this result is in line with a study conducted with Nofal et al [45] who confirmed the safety of A. judaica extracts.…”
Section: Discussionsupporting
confidence: 82%
“…The protective role of A. judaica may be ascribed to its powerful free radical scavenger activity [38,39]. Furthermore, A. judaica was revealed to have sesquiterpene lactones [36] flavonoids [35,40] and high phenolic contents [39,41,43]. These compounds were reported to have multiple biological effects including antiinflammatory, antioxidant [43] chemopreventive and anticancer activities [44].…”
Section: Discussionmentioning
confidence: 99%
“…It provides efficient protection against oxidative damage caused by reactive species like peroxide and superoxide radicals which cause serious damage to biological systems. [25][26][27][28] Green tea extract contains mainly four types of catechins, (2)-epigallocatechingallate (EGCG), (2)-epigallocatechin (EGC), (2)-epicatechin-gallate (ECG), and (2)-epicatechin (EC) [29,30] of which EGCG and ECG contain the gallic acid moiety. Although EGCG is the most abundant catechin [31] the maximum antioxidant property is shown by ECG.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, the importance of choosing the different fruit that in combination of their antioxidants may be advantage when designing functional foods. As we mentioned before [44], more studies with combinations are required in a more mechanistic way, including infrared spectrometry and magnetic nuclear resonance, in order to better understand the mechanisms that are taking place inside an antioxidant system. Also, further studies are needed to evaluate the bioabsortion, biodisponibility and interactions between these compounds present in papaya pulp and other tropical fruits, after consumption.…”
Section: Evaluation Of the Individual And Combinedmentioning
confidence: 99%
“…Palafox-Carlo [44] reported the interactions that occur between major phenolics present in "Ataulfo" mango. These authors observed that gallic and protocatechuic acid exhibited the highest antioxidant capacity, probably due to their particular chemical conformation and hydroxyl groups content.…”
Section: Evaluation Of the Individual And Combinedmentioning
confidence: 99%